The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.2174/138920007780362545
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Targeting of IDO-Mediated Tolerance for Treating Autoimmune Disease

Abstract: Cells at the maternal-fetal interface express indoleamine 2,3 dioxygenase (IDO) to consume all local tryptophan for the express purpose of starving adjacent maternal T cells of this most limiting and essential amino acid. This stops local T cell proliferation to ultimately result in the most dramatic example of immune tolerance, acceptance of the fetus. By contrast, inhibition of IDO using 1-methyl-tryptophan causes a sudden catastrophic rejection of the mammalian fetus. Immunomodulatory factors including IFNg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 240 publications
(323 reference statements)
1
51
0
Order By: Relevance
“…It has been shown that stimulation of costimulatory molecules (CTLA-4 and CD80/86) or TLR upregulates IDO1 in inflammatory sites, through IFN-a-dependent pathways (19). Treatment of MBP-peptide-specific T cells with TLR3 agonist polyinosinicpolycytidylic acid significantly increased IDO expression (Fig.…”
Section: Induction Of Ido1 By Ctla-4 or Tlr-3 Ligation Dampens Proinfmentioning
confidence: 87%
“…It has been shown that stimulation of costimulatory molecules (CTLA-4 and CD80/86) or TLR upregulates IDO1 in inflammatory sites, through IFN-a-dependent pathways (19). Treatment of MBP-peptide-specific T cells with TLR3 agonist polyinosinicpolycytidylic acid significantly increased IDO expression (Fig.…”
Section: Induction Of Ido1 By Ctla-4 or Tlr-3 Ligation Dampens Proinfmentioning
confidence: 87%
“…Given the importance of intracellular NAD + levels for maintaining overall cellular integrity and function, it is conceivable that reduced NAD + levels are a potential pathogenic mechanism for neuronal and astroglial cell death 11,8. TRP has been used as a supplement for some years in the United States before being removed due to an outbreak of the lethal autoimmune disease, eosinophilia-myalgia syndrome (EMS) resulting in 36 deaths 11. Large doses of TRP can induce the build-up of selected white blood cells leading to EMS.…”
Section: Discussionmentioning
confidence: 99%
“…Essential NAD + dependent reactions can be divided into three main categories:2 (1) NAD + is an important contributor to energy (ATP) production;3 (2) NAD + serves as a cofactor for NAD glycohydrolases involved in intracellular calcium regulation;4,5 (3) NAD + is a substrate for the family of DNA nick sensing poly(ADP-ribose) polymerases (PARP)68 and the class III histone deacetylases known as sirtuins 9,10. NAD + levels are extremely volatile and can be significantly reduced under conditions of excessive PARP-1 activation caused by oxidative damage to DNA, and during mitosis 11. Thus, continuous biosynthesis of NAD + is vital to the maintenance and ongoing cell viability of all cells 12…”
Section: Introductionmentioning
confidence: 99%
“…IDO-1 also creates a hostile environment that prevents the invasion of microbes such as pathogenic bacteria and viruses 97 . Moreover, IDO-1 reduces pathogen growth and decreases asthma severity in a model of pulmonary disease activated by TLR9 agonists 98,99 .…”
Section: Modulation Of Gcn2 By Amino Acid Deprivation and Pro-inflammmentioning
confidence: 99%